Evolution of the Polyphenol and Terpene Content, Antioxidant Activity and Plant Morphology of Eight Different Fiber-Type Cultivars of Cannabis sativa L. Cultivated at Three Sowing Densities - Amandine André; Marianne Leupin; Markus Kneubühl; Vasilisa Pedan; Irene Chetschik (Plants, 2020)
The chemical composition of the inflorescences of eight different fibre-type Cannabis sativa L. cultivars grown in Switzerland was monitored for different sowing densities over the season 2019. HPLC-MS, GC-MS and GC-FID, as well as spectrophotometric techniques were used to measure the total phenolic content (TPC) and the antioxidative activity of the inflorescence extracts, and to characterise and quantify the flavonoids and terpenes produced by the different cultivars over different sowing densities from July to September 2019. The main finding of the present study is that the TPC, as well as the individual flavonoids and terpenes, were mainly influenced by the harvest period and the phenological stage of the plant. The content of polyphenols and flavonoids decrease during the flower development for all cultivars studied. The terpene content increased with maturation. The monoterpenes/sesquiterpenes ratio also changed between the early flowering (majority of sesquiterpenes) and the end of flowering (majority of monoterpenes). The sowing density showed an impact on plant morphology, a low density such as 30 seeds/m2 influencing the production of bigger flowers, thus increasing the yield of polyphenols and terpenes production. Therefore, hemp inflorescences can be regarded as valuable by-products of fibre production, for their valorisation in the food and beverage industry in addition to cosmetics and perfumery.